Kajian Valuasi Ekonomi Hutan Mangrove Di Desa Pasar Banggi, Kecamatan Rembang, Kabupaten Rembang - Hanifa, Aurora; Pribadi, Rudhi; Nirwani, Nirwani (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Economi valuation is an instrument used to know a function of mangrove forest. The object of this research are to find out totalized economic valuation by means of direct valuation at mangrove area Pasar Banggi village, Rembang. Economic valuation can be able by totalized a direct use value, indirect use value, Option value and Existence value. Identification result at Pasar Banggi village are consist by four components there are, direct use values : Bandeng fishponds, saltponds, mangrove seeds, catching fishes, oyster and crab, indirect use values : breakwater as a resists of abration, option value : biodiversity, Existence value : habitats. The biggest value in this research is the resist of abration assumption as breakwater that is as bis as Rp.18.717.774.250-/year and total economic value from economis Pasar Banggi village, Rembang that is as big as Rp.19.610.846.229.-/year.